Purification and partial characterization of human lymphoblast interferon. - Zoon, K C (1979)
One component of human lymphoblastoid interferon obtained from Namalwa cultures induced by Newcastle disease virus has been purified to a specific activity of 2.5 x 10(8) interferon units per mg of protein (protein content based on amino acid analysis). A single polypeptide species with an apparent molecular weight of 18,500 comigrating with the antiviral activity was observed by sodium dodecyl sulfate/polyacrylamide gel electrophoresis. Preliminary amino-terminal sequencing results support the conclusion that the interferon species is essentially homogeneous.